αvβ3 Integrin Antagonists Enhance Chemotherapy Response in an Orthotopic Pancreatic Cancer Model - Debreli Coskun, Melis; Sudha, Thangirala; Bharali, Dhruba J.; Celikler, Serap; Davis, Paul J.; Mousa, Shaker A. (Frontiers in Pharmacology, 2020)
Pancreatic cancer decreases survival time and quality of life because of drug resistance and peripheral neuropathy during conventional treatment. This study was undertaken to investigate whether αvβ3 integrin receptor antagonist compounds NDAT and XT199 can suppress the development of cisplatin resistance and cisplatin-induced peripheral neuropathy in an orthotopic pancreatic SUIT2-luc cancer cell mouse model. Anticancer effects of these compounds and their combination with cisplatin were assessed in this tumor mouse model with bioluminescent signaling and histopathology, and a cytokine assay was used to examine expression of inflammatory cytokines IL-1β, IL-6, IL-10, and TNF-α from plasma samples. To determine the neuroprotective effects of the compounds on cisplatin-induced peripheral neuropathy, behavioral hind-limb posture of the mice was evaluated. The combination therapy of NDAT or XT199 with cisplatin elicited greater inhibition of tumor growth and increased tumor necrosis compared to cisplatin alone. NDAT and XT199 in combination with cisplatin significantly decreased expression of pro-inflammatory cytokines IL-1β, IL-6 and TNF-α and significantly increased expression of anti-inflammatory cytokine IL-10 in comparison to cisplatin alone. Cisplatin-treated groups showed stocking-glove hind-limb posture, whereas NDAT and XT199 with cisplatin-treated groups displayed normal hind-limb posture. Results clearly suggest that NDAT and XT199 treatment with cisplatin that inactivates NF-κB may contribute to increased antitumor and anti-inflammatory efficacy as well as alleviate cisplatin-mediated loss of motor function in this pancreatic tumor mouse model.